Design and implementation of a DNP3-based SCADA system with internet and WAP access - Sandro, Jennibeth D. (2007)
Supervisory Control and Data Acquisition (SCADA) systems enable master stations to monitor and control distributed field equipment. Recent developments in industry-standard communication protocols and networking technologies have allowed SCADA systems to deviate from traditional implementation that operate only in closed networks. We present an implementation of a web-based SCADA system that makes use of the Distributed Network Protocol (DNP3), a communication protocol designed for electric utility SCADA. The system components interconnect over the Local Area Network, and communicate via DNP3 over TCP/IP. The features of the SCADA software include alarm logging, historical logging, data trending, user authentication, and WAP browser support.